Operational Challenges and Management Strategies Affecting Emergency Department Length of Stay: A Literature Review - Vindy Vanessa Wennas (Institute of Advanced Knowledge and Science, 2026)
Emergency department (ED) length of stay (LOS) is an important indicator of healthcare quality and operational efficiency. Prolonged ED LOS contributes to overcrowding, delays in treatment, morbidity, mortality, and reduced patient satisfaction. Numerous studies have examined factors associated with ED LOS, but evidence remains fragmented when viewed through the input-throughput-output conceptual framework. This review aimed to evaluate operational challenges affecting ED LOS and identify management strategies to improve patient flow. A literature search was conducted in PubMed and Google Scholar for studies published between 2021 and 2026. Title and abstract screening were conducted, and relevant full-text articles written in English were included. Three major operational challenges affecting ED LOS were identified. Input factors were related to ED overcrowding, which was associated with increased patient congestion, delayed triage, and prolonged LOS. Throughput factors included physician workload and nurse shortages, which negatively affected patient flow and care delivery. Output factors were dominated by boarding and access block, which were also associated with prolonged LOS, adverse patient outcomes, and increased mortality risk. Several management strategies were identified, including fast-track triage systems, physician-to-nurse teams, boarding-restriction protocols, and optimized bed-allocation models. In conclusion, overcrowding, staffing, and boarding are key operational challenges influencing ED LOS, and they are interconnected and addressed through coordinated strategies. Among them, boarding appears to have a greater influence on operational bottlenecks because it affects ED process efficiency, hospital-wide patient flow, and bed management. Strategies targeting boarding may provide broader improvements in ED LOS while simultaneously alleviating overcrowding, staff shortages, and workload.